ABO-incompatible living donor liver transplantation in a patient with a history of platelet transfusion-related anaphylaxis - Won-Bae Chang; Ho-Seong Han; Jai Young Cho; Yoo-Seok Yoon; Young Rok Choi; Bo-Ram Lee (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Anaphylaxis and severe allergic transfusion reactions (ATR) are uncommon complications after blood transfusion. Nevertheless, these complications are associated with very severe outcomes, such as dyspnea, shock, and death. Patients with end-stage liver disease who require liver transplantation have a high tendency for bleeding because of splenomegaly-induced thrombocytopenia and decreased production of coagulation factors in the liver. Liver transplantation is a very long procedure and a significant perioperative blood loss is highly likely. Therefore, transfusion of platelets and other blood products is often necessary. We report a successful ABO-incompatible living donor liver transplantation in a patient with hepatitis B virus-related liver cirrhosis and hepatocellular carcinoma who had a history of platelet transfusion-related anaphylaxis.